![image](https://tex.z-dn.net/?f=1%29%5C+3ctg%283x%29-%5Csqrt3%3D0%3B+%5C+x%5C+%5B%5Cfrac%7B%5Cpi%7D%7B6%7D%3B%5Cpi%5D%5C%5C%0A3ctg%283x%29-%5Csqrt3%3D0%5C%5C%0A3ctg%283x%29%3D%5Csqrt3%5C%5C%0Actg%283x%29%3D%5Cfrac%7B%5Csqrt3%7D%7B3%7D%5C%5C%0A3x%3D%5Cfrac%7B%5Cpi%7D%7B3%7D%2B%5Cpi+k%5C%5C%0Ax%3D%5Cfrac%7B%5Cpi%7D%7B9%7D%2B%5Cfrac%7B%5Cpi+k%7D%7B3%7D%3B%5C+x%5C+%5B%5Cfrac%7B%5Cpi%7D%7B6%7D%3B%5Cpi%5D%5C%5C%0A%5Cfrac%7B%5Cpi%7D%7B6%7D+%5Cleq+%5Cfrac%7B%5Cpi%7D%7B9%7D%2B%5Cfrac%7B%5Cpi+k%7D%7B3%7D+%5Cleq+%5Cpi%5C%5C%0A%5Cfrac%7B1%7D%7B6%7D+%5Cleq+%5Cfrac%7B1%7D%7B9%7D%2B%5Cfrac%7Bk%7D%7B3%7D+%5Cleq+1%5C%5C%0A%5Cfrac%7B1%7D%7B18%7D+%5Cleq+%5Cfrac%7Bk%7D%7B3%7D+%5Cleq+%5Cfrac%7B8%7D%7B9%7D%5C%5C%0A%5Cfrac%7B1%7D%7B6%7D+%5Cleq+k+%5Cleq+2+%5Cfrac%7B2%7D%7B3%7D%5C+%3D%3E%5C+k%3D1%3B+2%5C%5C%0Ak%3D1%5C+%3D%3E%5C+x%3D%5Cfrac%7B%5Cpi%7D%7B9%7D%2B%5Cfrac%7B%5Cpi%7D%7B3%7D%3D%5Cfrac%7B4%5Cpi%7D%7B9%7D%5C%5C)
\ k=1; 2\\
k=1\ =>\ x=\frac{\pi}{9}+\frac{\pi}{3}=\frac{4\pi}{9}\\" alt="1)\ 3ctg(3x)-\sqrt3=0; \ x\ [\frac{\pi}{6};\pi]\\
3ctg(3x)-\sqrt3=0\\
3ctg(3x)=\sqrt3\\
ctg(3x)=\frac{\sqrt3}{3}\\
3x=\frac{\pi}{3}+\pi k\\
x=\frac{\pi}{9}+\frac{\pi k}{3};\ x\ [\frac{\pi}{6};\pi]\\
\frac{\pi}{6} \leq \frac{\pi}{9}+\frac{\pi k}{3} \leq \pi\\
\frac{1}{6} \leq \frac{1}{9}+\frac{k}{3} \leq 1\\
\frac{1}{18} \leq \frac{k}{3} \leq \frac{8}{9}\\
\frac{1}{6} \leq k \leq 2 \frac{2}{3}\ =>\ k=1; 2\\
k=1\ =>\ x=\frac{\pi}{9}+\frac{\pi}{3}=\frac{4\pi}{9}\\" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=k%3D2%5C+%3D%3E%5C+x%3D%5Cfrac%7B%5Cpi%7D%7B9%7D%2B%5Cfrac%7B2%5Cpi%7D%7B3%7D%3D%5Cfrac%7B7%5Cpi%7D%7B9%7D%5C%5C%0A2%29%5C+sin%28x-%5Cfrac%7B%5Cpi%7D%7B6%7D%29%3D-%5Cfrac%7B%5Csqrt3%7D%7B2%7D%3B%5C+x%3E0+%5C%5C%0A%7Cx-%5Cfrac%7B%5Cpi%7D%7B6%7D%3D-%5Cfrac%7B%5Cpi%7D%7B6%7D%2B2%5Cpi+k%5C%5C%0A%7Cx-%5Cfrac%7B%5Cpi%7D%7B6%7D%3D-%5Cfrac%7B5%5Cpi%7D%7B6%7D%2B2%5Cpi+k%5C%5C%0A%5C%5C%0A%7Cx%3D2%5Cpi+k%5C%5C%0A%7Cx%3D-%5Cfrac%7B2%5Cpi%7D%7B3%7D%2B2%5Cpi+k%5C%5C%0Ax%3E0%5C%5C%0A%5C%5C%0A%7C2%5Cpi+k%3E0+%5C+%3D%3E%5C+x%3D2%5Cpi%3E0%28k%3D0+%5C+%3D%3E%5C+x%3D0%29%5C%5C%0A%7C-%5Cfrac%7B2%5Cpi%7D%7B3%7D%2B2%5Cpi+k+%3E0%5C+%3D%3Ek%3D0%3B+x%3D-%5Cfrac%7B2%5Cpi%7D%7B3%7D%3C0%5C+%3D%3E%5C+k%3D1%3B%5C+x%3D-%5Cfrac%7B2%5Cpi%7D%7B3%7D%2B%5C%5C%0A%2B2%5Cpi%3D%5Cfrac%7B4%5Cpi%7D%7B3%7D%3E0%5C%5C%0A%5Cfrac%7B4%5Cpi%7D%7B3%7D%3C2%5Cpi%5C%5C)
\ x=\frac{\pi}{9}+\frac{2\pi}{3}=\frac{7\pi}{9}\\
2)\ sin(x-\frac{\pi}{6})=-\frac{\sqrt3}{2};\ x>0 \\
|x-\frac{\pi}{6}=-\frac{\pi}{6}+2\pi k\\
|x-\frac{\pi}{6}=-\frac{5\pi}{6}+2\pi k\\
\\
|x=2\pi k\\
|x=-\frac{2\pi}{3}+2\pi k\\
x>0\\
\\
|2\pi k>0 \ =>\ x=2\pi>0(k=0 \ =>\ x=0)\\
|-\frac{2\pi}{3}+2\pi k >0\ =>k=0; x=-\frac{2\pi}{3}<0\ =>\ k=1;\ x=-\frac{2\pi}{3}+\\
+2\pi=\frac{4\pi}{3}>0\\
\frac{4\pi}{3}<2\pi\\" alt="k=2\ =>\ x=\frac{\pi}{9}+\frac{2\pi}{3}=\frac{7\pi}{9}\\
2)\ sin(x-\frac{\pi}{6})=-\frac{\sqrt3}{2};\ x>0 \\
|x-\frac{\pi}{6}=-\frac{\pi}{6}+2\pi k\\
|x-\frac{\pi}{6}=-\frac{5\pi}{6}+2\pi k\\
\\
|x=2\pi k\\
|x=-\frac{2\pi}{3}+2\pi k\\
x>0\\
\\
|2\pi k>0 \ =>\ x=2\pi>0(k=0 \ =>\ x=0)\\
|-\frac{2\pi}{3}+2\pi k >0\ =>k=0; x=-\frac{2\pi}{3}<0\ =>\ k=1;\ x=-\frac{2\pi}{3}+\\
+2\pi=\frac{4\pi}{3}>0\\
\frac{4\pi}{3}<2\pi\\" align="absmiddle" class="latex-formula">
Ответ: